Is Credit System Serving Three Types of Students? Teacher and Student Perspectives in the Implementation of Mathematics Learning - Sumbaji Putranto; Gamarina Isti Ratnasari; Habibullah Habibullah (JNPM (Jurnal Nasional Pendidikan Matematika), 2022)
Abstract. Students should receive educational services according to their talents, interests, and abilities. Therefore, a learning system should accommodate fast, normal, and slow learners. This study aims to identify the perspective of teachers and second graders on the application of the Credit System in Yogyakarta secondary schools, the constraints, as well as strategies in implementing the Credit System. The study is phenomenological research. The data was collected using interviews and focus group discussion results. The participants were students and teachers who carried out the Credit System for learning mathematics. The data analysis was done using the Bogdan & Biklen approach. The results of the study show that teachers and students still find difficulty carrying out credit systems. The causes of these students' perspectives are that students are not used to learning independently and teachers are still confused about doing Credit Systems learning to serve all types of students. The strategy of this challenge is to add hours to types of fast learner and teachers make modules that are easy to understand for all types of learner.Keywords: credit system, mathematics, teacher and student perspective.Â